2021
DOI: 10.1016/j.cub.2021.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Between-subject prediction reveals a shared representational geometry in the rodent hippocampus

Abstract: The rodent hippocampus constructs statistically independent representations across environments (''global remapping'') and assigns individual neuron firing fields to locations within an environment in an apparently random fashion, processes thought to contribute to the role of the hippocampus in episodic memory. This random mapping implies that it should be challenging to predict hippocampal encoding of a given experience in one subject based on the encoding of that same experience in another subject. Contrary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Our finding of a preserved structure of population activity both in time and across subjects bears similarity to and extends upon previous reports: Stable latent dynamics of population activity despite changing cell identities on different recording days have been observed in monkey motor cortex upon learning of a motor task [34]. Moreover, latent dynamics of population activity in motor cortex [35], orbitofrontal cortex [36], and hippocampus [37][38][39] are preserved across individuals executing learned tasks and appear in sensory-motor cortex during foraging for rewards [40]. Our results imply that stable and preserved population activity patterns are not restricted to cognitive or motor behaviors but that they also characterize the mPFC during innate stress coping.…”
Section: Plos Biologysupporting
confidence: 90%
“…Our finding of a preserved structure of population activity both in time and across subjects bears similarity to and extends upon previous reports: Stable latent dynamics of population activity despite changing cell identities on different recording days have been observed in monkey motor cortex upon learning of a motor task [34]. Moreover, latent dynamics of population activity in motor cortex [35], orbitofrontal cortex [36], and hippocampus [37][38][39] are preserved across individuals executing learned tasks and appear in sensory-motor cortex during foraging for rewards [40]. Our results imply that stable and preserved population activity patterns are not restricted to cognitive or motor behaviors but that they also characterize the mPFC during innate stress coping.…”
Section: Plos Biologysupporting
confidence: 90%
“…However, in theory, the algorithm itself can be applied to any kind of data matrices. In our previous hyperalignment algorithms, the searchlight procedure originally developed based on response profiles (RHA) (Feilong et al, 2018; Guntupalli et al, 2016; Haxby et al, 2020; Jiahui et al, 2020) has been applied successfully to connectivity profiles (CHA) (Feilong et al, 2021; Guntupalli et al, 2018; Nastase et al, 2020) and a hybrid of both (H2A) (Busch et al, 2021); and the original algorithm developed based on fMRI data of humans (Haxby et al, 2011) has been applied successfully to electrophysiology recording data of rodent neurons (Chen et al, 2021). We leave it to future works to assess the generalizability of the INT model to other functional profiles, modalities, and species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Safaie et al used similar alignment techniques to show that latent signals in M1 were preserved across monkeys as they performed a center-out reaching task using a planar manipulandum; latent signals were also preserved in the dorsolateral striatum of mice that grasped and pulled a joystick (Safaie et al 2022). Other recent studies revealed that low-dimensional neural structure within the hippocampus and the sensorimotor cortex is preserved across rats for a variety of behaviors, ranging from locomotion along a linear track inside a maze to unconstrained movement in an arena (Rubin et al 2019, Chen et al 2021, Nieh et al 2021, Melbaum et al 2022.…”
Section: Neural Representations Of Motor Intent Are Similar Across Mo...mentioning
confidence: 96%